Quo vadis, Geldmenge? Zur Rolle der Geldmenge für eine moderne Geldpolitik - Egon Görgens; Karlheinz Ruckriegel; Franz Seitz (Research On Money in the Economy (ROME), 2007)
– What role does (should) money play in modern central banking? To answer this question, it is necessary to distinguish between the different level playing fields of monetary policy. At the operational level, it is a short-term money market rate which the central bank tries to and can control. Therefore, monetary policy should be described in terms of an interest-rate feedback relation. Consequently, base money is an endogenous variable. This has been taken into account by the now-standard New-Keynesian macro models. As in these models money is a redundant variable, we extend the model to incorporate the money-price-nexus. Furthermore, we analyse what useful information monetary analysis can deliver for central banks both in theory and in practice. In sum, we find that ignoring the indicator properties of money in the transmission process would unduly restrain monetary policy.
Keywords: E42; E52; E58; 330; Geld; Geldpolitik; Indikator; Neu-Keynesianische Modelle; Reaktionsfunktion